(untitled) (Journal of Computational Mathematics, 2021)
In this paper, we consider solving dense linear equations on Dawning1000 by using matrix partitioning technique. Based on this partitioning of matrix, we give a parallel block LU decomposition method. The efficiency of solving linear equations by different ways is analysed. The numerical results are given on Dawning1000. By running our parallel program, the best speed up on 32 processors is over 25.